DAMPING OF CIRCULAR COMPOSITE VISCOELASTIC PLATE VIBRATION UNDER NEUTRON IRRADIATION - Vakhneev, Sergey N.; Starovoitov, Eduard I. (Journal of Applied Engineering Science, 2020)
During the irradiation of structural elements with neutrons, ions, electrons, the mechanical properties of materials change. The neutron irradiation is of particular interest. Therefore, the relevance of the study is beyond doubt. The main purpose of this paper is to investigate the vibration damping of a circular composite viscoelastic plate under neutron irradiation. According to existing concepts, two mechanisms of accelerated radiation creep are possible. An initial-boundary value problem of free vibrations damping in a circular linearly viscoelastic sandwich plate under neutron irradiation is considered. It is determined that when the frequency of the perturbing force coincides with higher frequencies of natural oscillations, the periodicity is blurred, although the amplitude of oscillations increases and, in this case, a "false resonance" is observed. An analytical solution is obtained using the averaging method in dynamic viscoelasticity problems. The logarithmic decrement of oscillations is investigated numerically. Its dependence on the intensity of the neutron flux is revealed.